Structural and functional state of bone tissue in young people with a combined course of osteoarthritis and obesity - Anastasiia Litvynova (Bogomolets National Medical University, 2022)
In recent years, an increase in the number of patients with osteoarthritis (ОА) against the background of obesity is considered not from the point of view of mechanical stress on the joints by an overweight patient but by the active synthesis of hormone-like substances by adipose tissue, which have a metabolic effect on all processes in the body. A large number of different chemical compounds (calcium, phosphorus, magnesium, uronic acids, tartrate-resistant bone phosphatase, and a number of others) are involved in the remodeling of bone tissue, the balance between which determines the strength and mobility of the bone. Among such biochemical markers, the glycoprotein osteoprotegerin is considered. The osteoprotegerin inhibits the differentiation of osteoclast precursors into osteoclasts and also regulates their resorption in vitro and in vivo. It works by binding to RANKL on osteoblast / stromal cells, thereby blocking the RANKL-RANK ligand interaction between osteoblasts / stromal cells and osteoclast precursors.The aim of our study to establish the content of osteoprotegerin in the blood serum of young patients with osteoarthritis and obesity and to analyze its role in the formation of structural and functional changes in bone tissue. The work was performed on 75 young patients (average age - 30.92 ± 0.55 years) with OA, which was established in patients with various stages of obesity; for the comparison group, 50 individuals with an isolated course of OA of the same age (30.95 ± 0.55 years) and duration of anamnesis were selected; control indicators were obtained when examining 37 apparently healthy individuals. The diagnosis of OA was confirmed by a comprehensive assessment of patients' complaints, anamnesis data, objective and instrumental studies (X-ray examination of the affected joints) while focusing on the "Protocols for the management of patients with osteoarthritis." The presence and severity of obesity were assessed according to the criteria of the International Diabetes Federation (IDF, 2005) based on the calculation of body mass index (BMI) according to the Kettle formula. The indicator of osteoprotegerin (pg / ml) (bone tissue glycoprotein) was investigated in fasting blood serum by enzyme-linked immunosorbent assay (ELISA) using FineTest EH0247 reagents, China. The prevalence of osteoporotic conditions was assessed by dual-energy X-ray absorptiometry (DEXA) using the HOLOGIC Explorer QDR W Series Bone Densitometer (USA). The content of osteoprotegerin in blood serum was studied as a biochemical marker of damage to the bone and cartilage tissue. The data obtained allowed us to say that in both groups - patients with OA (92.3 ± 1.68 pg / ml) and patients with a combination of OA with obesity and increased body weight (124.03 ± 3.2 pg / ml) - there was an increase in this glycoprotein when compared with the control values ​​(65.64 ± 0.64), (p <0.001). The performed densitometric study allowed us to obtain the following results: osteopenia was identified in 15% of patients in main group and in 36% - in comparison group; osteoporosis was identified in 24% of patients in main group and in 10% - in comparison group.The course of osteoarthritis in young people is accompanied by the formation of osteoporotic conditions, which more often (24% versus 10%), with the addition of obesity, lead to the development of osteoporosis. The development of osteoporotic changes in patients with osteoarthritis and in combination with obesity is accompanied by an increase in the synthesis of osteoprotegerin, a glycoprotein involved in the processes of bone tissue remodeling.